Effect of Glycerol Modification on Mn-Doped ZnO–Chitosan Membranes for Tartrazine Photodegradation - Nur Faridatus Soimah; Khabibi Khabibi; Retno Ariadi Lusiana (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
This study evaluates the photocatalytic performance and charge transfer behavior of Mn-doped ZnO chitosan membranes, both with and without glycerol, for the degradation of tartrazine under visible light. The membranes were prepared by homogeneous mixing using chitosan as the polymer matrix, ZnO as the photocatalyst, Mn2+ as the dopant, and glycerol as a plasticizer. Membrane morphology and elemental distribution were examined using SEM and EDX, and supported by physical tests. Glycerol increased membrane flexibility and mechanical strength, but reduced porosity and surface hydrophilicity, indicating a denser polymer network and water accessibility. Photocatalytic activity was quantified from UV Vis monitoring of tartrazine and fitted to pseudo-first-order kinetics. The glycerol-containing membrane showed a higher rate constant (k = 0.4398 h−1) than the membrane without glycerol (k = 0.0893 h−1). The performance improvement is attributed to better catalyst retention and dispersion in the matrix, which supports photon utilization and charge separation. Mechanistic interpretation suggests that Mn2+ acts as an electron trap, thereby suppressing electron-hole recombination and promoting the formation of reactive species. At the same time, glycerol can suppress the generation of hydroxyl and superoxide radicals by limiting contact among tartrazine, water, and photocatalytically active sites. Overall, the results reveal a trade-off between transport properties and catalytic efficiency, identifying glycerol content as a key parameter for optimizing Mn-doped ZnO chitosan membranes for dye wastewater treatment.